2014
DOI: 10.3892/or.2014.3256
|View full text |Cite
|
Sign up to set email alerts
|

Using [18F]FBAU for imaging brain tumor progression in an F98/tk-luc glioma-bearing rat model

Abstract: 1-(2-Deoxy-2-[18F]fluoro-β-D-arabinofuranosyl)-5-bromouracil ([18F]FBAU), a substitute for thymine, has been reported as an effective reporter probe by which to trace cellular metabolism with its positron emission. In the present study, a rat xenograft model bearing F98 glioma transfected with dual reporter genes, herpes simplex virus type 1 thymidine kinase (HSV1-tk) and firefly luciferase (luc) was used for monitoring tumor progression by multimodalities of molecular imaging using [18F]FBAU and D-luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Both image techniques had good correlation when compared with BLI signal and MRI tumor volume at each time point measured for tumor growth monitoring. Studies about glioma tumor model reported this correlation with excellent results [ 30 32 ]. However, this correlation can change at later stages of tumor growth.…”
Section: Discussionmentioning
confidence: 68%
“…Both image techniques had good correlation when compared with BLI signal and MRI tumor volume at each time point measured for tumor growth monitoring. Studies about glioma tumor model reported this correlation with excellent results [ 30 32 ]. However, this correlation can change at later stages of tumor growth.…”
Section: Discussionmentioning
confidence: 68%
“…In the pilot rat model, the growth of GBM was successfully followed up with correlated luminescence signal in which the correlation efficiency was about 0.85 [29]. Following their example, in 2014, our team had successfully extended the applications of GBM animal model to a double-reporter gene F98/tk-luc tumor-bearing rat model, whose bioluminescence signals can be accurately detected with multimodality imaging instruments [30]. In that module, the growth of in situ brain tumor was visible and quantitatively followed up with the expressions of luc and HSV1-tk, enlightening the access to examine the feasibility of candidates to serve as GBM drugs and/or radiosensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…Combined genetically encoded molecular imaging probes with nuclear medicine tomography are widely used in tumor imaging, mainly including tracking cell levels, monitoring Contrast Media & Molecular Imaging cancer progression and metastasis, and evaluating the efficacy of anticancer therapy. For example, the herpes simplex virus type 1 thymidine kinase (HSV1-TK) genetic sequence was designed to selectively uptake 18F to locate and track therapeutic substances in glioma [54].…”
Section: Nuclear Medicine Imaging Nuclear Medicine Imaging Mainly Inc...mentioning
confidence: 99%